Preparation and characterisation of heat treated oil palm-empty fruit bunch/high density polyethylene composites / Nur Afifah Nordin - Nur Afifah , Nordin (2020)
Natural fibre composites (NFCs) are composite materials, in which the reinforcing fibres are derived from renewable and carbon dioxide neutral resources such as wood or plants. NFC can be made by replacing synthetic fibres with various types of natural fibres. Oil palm empty fruit bunch (OPEFB) fibre and oil palm mesocarp fibre are two important types of fibrous materials left in the palm-oil industry. In this study, EFB will be used as a reinforcement to the high-density polyethylene (HDPE). EFB was heat-treated at 180°C using vacuum oven for one hour, extrusion compounded with HDPE at 10%, 20% and 30% weight fraction. The composites then were injection moulded into dumb-bell and bar shaped specimens using a Boy® 55M injection moulding machine. All of the composites were exposed to different environments and the effects of conditioning were discussed relative to the sample in dry as moulded condition as reference. The effects of composition and heat treatment on the thermal properties of composites were investigated using Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). The tensile and flexural tests were also done using an Instron Universal Testing Machine. The impact test was run under Charpy mode using an Instron Dynatup 9210 instrumented falling weight impact tester with a V-shape impactor tup. TGA shows an increase in degradation peak temperature of the heat-treated composites. DSC results revealed that EFB had no significant effect on the melting behaviour of the composites. However, an increasing trend in the degree of crystallinity (Xc) of the composite is observed as the heat treated EFB was used in the system. An increment in the tensile modulus and tensile strain were observed for the treated fibre composites due to the improved wetting between fibre and matrix. Hence, leading to better interfacial adhesion between them. In addition, the tensile strength value was increased for treated fibre composites with lower fibre loading. In impact tests, the fracture energy (W) of composites increased with increasing of fibre content. However, the critical strain energy release rate decreases with increasing of fibre content. In addition, the peak load (P) and critical stress intensity factor (Kc) increased with fibre contents. Moreover, the value of P, W, Kc and Gc increased with fibre treatment. All composites absorb moisture to various extents with the untreated fibre composites show the highest value of absorption. Thermal and mechanical properties reduced after soil burial on the composites. For that condition, composites made from heat treated EFB shows better thermal stability due to the improved compatibility between fibres and matrices, thus lowering the moisture intake, hence improve better thermal stability. Mechanical properties reduced due to attack of microorganisms that promote further composite degradation rate. The treated fibre composites showed more resistance towards the environment. However, indoor exposure has no significant effect on thermal and mechanical properties of composites. The MFI values of untreated and treated fibre composites decreased with the increase of EFB fibre loading in the system